Benchmarking of efficiency of accumulation and storage of hydrogen as a motor fuel - Бойченко, Сергій Валерійович; Калмикова, Наталія Григорівна (Science-based technologies, 2020)
The development of hydrogen energy and the need to find new efficient energy sources and develop on their basis environmentally friendly alternative fuels due to two main factors: the rapid depletion of oil reserves on Earth; deteriorating environmental situation in many countries, ahead in development. Today, the attractiveness of hydrogen as a universal energy source is determined by environmental friendliness, flexibility and efficient energy conversion processes for its participation. General work support is a comprehensive situational analysis (SNW-analysis, benchmarking) of the world experience of using hydrogen as a motor fuel, which includes identification of the best technologies, trends, features of use, research of advantages and disadvantages of technological accumulation and storage of hydrogen, and ways to achieve strategic goals for hydrogen technologies in the future. It is known that hydrogen as an environmentally friendly motor fuel is provided with high-tech methods of accumulation and storage, increases the minimization of emissions of harmful substances and can significantly improve the state of the technosphere. From these data, we concluded that the best technology for storing hydrogen as a motor fuel is compressed hydrogen gas. Because the existing models of tanks made of carbon fiber are light and reliable, as well as the hydrogen supply stored in them for 400-500 km of the car. The new materials section allows you to store hydrogen for a higher pressure. The best technology for the accumulation of hydrogen as a motor fuel is - fuel cells. A significant advantage of fuel cells is the quiet operation and the absence of harmful emissions during operation. The most effective is the use of fuel cells in cars. The best feature is that the use of fuel cells involves the use of chemical energy of the fuel converted into electricity that bypassing to the combustion processes.